THE EFFECT OF SELF-CONCEPT ON THE ACADEMIC PERFORMANCE OF SECONDARY SCHOOL STUDENTS IN IKOM LOCAL GOVERNMENT AREA OF CROSS RIVERS STATE - Charles Ekpung Akata; Nkanu Ovai Nkanu; Anietie Imo Effiong (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study investigated the effect of self-concept on the academic performance of secondary school students in Ikom Local Government Area of Cross River State, focusing on its relationship with academic outcomes, gender, and subject specialization. Method: A descriptive survey research design was employed, utilizing a validated instrument, the Self-Concept and Academic Performance Questionnaire (SCAPQ). A stratified random sampling technique selected 240 Senior Secondary School II students from six schools, with 228 valid responses analyzed. Data analysis involved descriptive statistics, Pearson Product-Moment Correlation, and independent samples t-tests at a 0.05 significance level. Results: Findings indicated a moderate, positive, and statistically significant relationship between self-concept and academic performance (r = 0.462, p < 0.05), while no significant differences were found across gender (t = 1.128, p = 0.260) or subject specialization (t = 0.559, p = 0.577). Novelty: This study contributes empirical evidence from Ikom L.G.A., highlighting self-concept as a universal academic resource that consistently supports students’ performance regardless of gender or discipline, and underscores the importance of targeted interventions in enhancing students’ self-beliefs for improved educational outcomes.